Uterine inversion with massive uterovaginal prolapse multiple bladder stones - Naidu, Aruku; Nusee, Zalina; Tayib, Shahila (Wiley-Blackwell Publishing Asia, 2011)
A non-puerperal uterine inversion in advanced uterovaginal prolapse is a rare occurrence. Even more unusual is the presence of bladder calculi in these two conditions, which has not been documented before. We report a case of acute urinary retention secondary to severe uterovaginal prolapse associated with uterine inversion and multiple bladder calculi.